Pengembangan Media Pembelajaran Video Interaktif Berbasis Power Director pada Materi Luas Segitiga - Firdaus, Alfi 'Inayatul; Sholihah, Ummu (Institut Agama Islam Negeri Curup, 2021)
This study aims to determine the validity and effectiveness of interactive video learning media based on Power Director in the area of the triangle material. The research approach used is the Research and Development (RnD) approach with the ADDIE (Analyze, Design, Development, Implementation, Evaluation) development model. The subjects in this study were class X-TOT 1 (control class) and class X-TOT 2 (Experimental Class). Methods of data collection using questionnaires and tests. Questionnaires were used to obtain media validity data and tests were used to determine the effectiveness of using media. The results showed that the Power Director-based interactive video learning media was valid for use with a media validity value of 3.02 and a material validity value of 3.7. The results of the t-test calculation carried out obtained a value of 0.001 <0.05 which indicates that there is a significant difference between the control class and the experimental class in the use of Power Director-based learning media. So, Power Director-based interactive video learning media is effectively used because it can improve student learning outcomes in solving the area of the triangle problem.